PENGARUH KOMPETENSI PROFESIONAL, PERSEPSI GURU TENTANG SISTEM MANAJEMEN MUTU DAN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU PADA SMK BER-ISO DI KOTA SALATIGA - Basuki, Edy Triyanto (2011)
Target this research is: 1) to analyze professional interest influence, perception learn about management system quality of, and leadership of headmaster by simultan to performance learn ISO Certivicated Vocational High School in Town Salatiga; 2) to analyze professional interest influence of teacher to performance learn ISO Certivicated Vocational High School in Town Salatiga; 3) to analyze perception influence learn about management system quality of to performance learn ISO Certivicated Vocational High School in Town Salatiga; and 4) for analyzing influence leadership of headmaster to performance learn ISO Certivicated Vocational High School in Town Salatiga. This population Research consist of ISO Certivicated Vocational High School teacher counted 116 people with sample to be checked of 90 people learn as responder. Research method wearied is quantitative method by analyze to use Multiple linear regression. Result of shown analysis that there are influence which is significant from professional interest, perception learn about management system quality of, and leadership of headmaster to performance learn ISO Certivicated Vocational High School in Town Salatiga either through individual and also simultan, shown the mentioned by acquirement assess significances at F test and t test < 0,05 (significances level 5%) so that raised hypothesis first, second , third, and fourth is proven in this research. Coefficient determinacy value (R2 ) having a meaning the level of free variable contribution (X) to variable tied (Y). Pursuant to result of examination obtained multiple linear regression R2 value (R Square) equal to 0,715 meaning the level of X variable influence (independent) to Y (dependent) equal to 71,5%, while the rest equal to 28,5% rendered by other factors which not explained in this research. Result of assumption test classical indicate that regression model [do] not experience of classic assumption problem or diffraction (normality, linearity, multicollinearity, and heteroscedasticity) so that can be expressed BLUE (Best, Linear, Unbiased, Estimator).